Financial Reporting Quality During COVID-19 Pandemic: International Evidence - Wan Adibah Wan Ismail,; Akmalia M. Ariff ,; Khairul Anuar Kamarudin,; Nur Shaida Mohd Adnan, (Asian Academy of Management Journal of Accounting and Finance, 2023)
This paper examines the effect of the COVID-19 pandemic on financial reporting quality proxied by earnings conservatism and value relevance of accounting information. Our final sample consists of 10,510 firm-year observations from 29 countries with a balanced number of 5,255 observations for pandemic and pre-pandemic periods. The results show that during the pandemic, the financial statements of companies with a financial year end of 31 March 2020 have different qualities than those in the pre-pandemic period. Lower earnings conservatism is demonstrated in the pandemic period compared to the pre-pandemic period, supporting the argument that business tends to slow the recognition of bad news as the pandemic starts. The value relevance of accounting information declined in the pandemic period, primarily affected by the reduced value relevance of the book value of equity. The findings of this study can help investors evaluate the quality of accounting information and make smarter investment decisions, especially when most companies are in financial trouble.